Digitalisasi Al-Bayyinah: Rekonstruksi Hukum Pembuktian Elektronik Dalam Perkara Perceraian Di Peradilan Agama - Miftakur Rohman (MASADIR: Jurnal Hukum Islam, 2025)
The digitalization of social interaction has emerged a new phenomenon in Islamic family law disputes, where digital evidence often becomes the primary instrument in court verification. However, judicial ambivalence remains in responding to digital evidence due to the rigid interpretation of the concept of al-bayyinah, which is still dominated by oral culture. This article aims to reconstruct the concept of evidence in Islamic family law to provide legitimacy for electronic evidence. Using a juridical-normative research method with a conceptual approach, this study examines Ibn Qayyim al-Jawziyya's thought on the flexibility of evidence. The results indicate that al-bayyinah should be understood as any means capable of revealing material truth, including verified digital data. This study proposes the construction of "Techno-Fiqh" as an integration framework between Islamic law and cyber law. The implications of this research emphasize that the independent recognition of digital evidence in Religious Courts is not merely a technical necessity, but an urgent ijtihad to achieve legal justice that is adaptive to modern changes.